Neoadjuvant chemotherapy for breast cancer - background for the indication of locoregional treatment - Krug, David; Wenz, Frederik (Strahlentherapie und Onkologie, 2018)
Neoadjuvant chemotherapy (NACT) has been widely adopted into the multidisciplinary management of breast cancer. The prognostic impact of treatment response has been clearly demonstrated. However, the impact of treatment response on the indication for adjuvant radiotherapy is unclear. This review summarizes important implications of NACT and treatment response on the risk of recurrence and locoregional multidisciplinary management from the standpoint of radiation oncology.